Spatiotemporal requirements of nuclear β-catenin define early sea urchin embryogenesis. - Guy Lhomond; Michael Schubert; Jenifer Croce (PLoS Biology)
Establishment of the 3 primordial germ layers (ectoderm, endoderm, and mesoderm) during early animal development represents an essential prerequisite for the emergence of properly patterned embryos. β-catenin is an ancient protein that is known to play essential roles in this process. However, these roles have chiefly been established through inhibition of β-catenin translation or function at the time of fertilization. Comprehensive analyses reporting the totality of functions played by nuclear β-catenin during early embryogenesis of a given animal, i.e., at different developmental stages and in different germ layers, are thus still lacking. In this study, we used an inducible, conditional knockdown system in the sea urchin to characterize all possible requirements of β-catenin for germ layer establishment and patterning. By blocking β-catenin protein production starting at 7 different time points of early development, between fertilization and 12 h post fertilization, we established a clear correlation between the position of a germ layer along the primary embryonic axis (the animal-vegetal axis) and its dependence on nuclear β-catenin activity. For example, in the vegetal hemisphere, we determined that the 3 germ layers (skeletogenic mesoderm, non-skeletogenic mesoderm, and endoderm) require distinct and highly specific durations of β-catenin production for their respective specification, with the most vegetal germ layer, the skeletogenic mesoderm, requiring the shortest duration. Likewise, for the 2 animal territories (ectoderm and anterior neuroectoderm), we established that their restriction, along the animal-vegetal axis, relies on different durations of β-catenin production and that the longest duration is required for the most animal territory, the anterior neuroectoderm. Moreover, we found that 2 of the vegetal germ layers, the non-skeletogenic mesoderm and the endoderm, further require a prolonged period of nuclear β-catenin activity after their specification to maintain their respective germ layer identities through time. Finally, we determined that restriction of the anterior neuroectoderm territory depends on at least 2 nuclear β-catenin-dependent inputs and a nuclear β-catenin-independent mechanism. Taken together, this work is the first to comprehensively define the spatiotemporal requirements of β-catenin during the early embryogenesis of a single animal, the sea urchin Paracentrotus lividus, thereby providing new experimental evidence for a better understanding of the roles played by this evolutionary conserved protein during animal development.